Quantitative methods in finance - Watsham, Terry J.; Parramore, Keith (London : International Thomson Business Press, 1997)
This booj is about: Interests rates and asset returns; Presentation of data and descriptive statistics; Calculus applied to finance; Probability distributions: applications to asset returns; Statistical inference: cnfidence intervals and hypothesis testing; Regression analysis; Time-series analysis; Numerical methods; Optimization; Continuous time mathematics in finance: asset prices as a stochastic process; and Multivariate analysis: principal components analysis and factor analysis.
Keywords: Finance; Mathemetics; Business mathematics; Business mathematics; Finance